2009
DOI: 10.1128/cvi.00092-09
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Polymorphic Peptides from GRA6 and GRA7 Sequences of Toxoplasma gondii Strains To Be Used in Serotyping

Abstract: The evaluation of Toxoplasma gondii isolates obtained from geographical environments other than Europe and North America revealed the existence of atypical strains that are not included in the three archetypal clonal lineages (lineages I, II, and III). GRA6 and GRA7 are polymorphic genes that have been used for the genotyping of Toxoplasma. The coding regions of GRA6 and GRA7 from 49 nonarchetypal strains were sequenced and compared with the sequences of type I, II, and III reference strains. Eighteen and 10 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 58 publications
2
52
0
2
Order By: Relevance
“…Therefore, a larger sample size should be carried out in human patients to identify specific T. gondii strains using high resolution typing methods such as multiplex nested PCR-RFLP which can genotype some DNA samples extracted directly from infected tissues. Serotyping of T. gondii strains has proved to be a promising tool using serum samples to overcome the diagnostic challenge (Kong et al, 2003;Peyron et al, 2006;Morisset et al, 2008;Sousa et al, 2008;Sousa et al, 2009). However, due to the limitation of serotyping it is not possible to differentiate type II from non-type II strains particularly in South America where there is a high diversity of T. gondii strain types.…”
Section: Other Diagnostic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a larger sample size should be carried out in human patients to identify specific T. gondii strains using high resolution typing methods such as multiplex nested PCR-RFLP which can genotype some DNA samples extracted directly from infected tissues. Serotyping of T. gondii strains has proved to be a promising tool using serum samples to overcome the diagnostic challenge (Kong et al, 2003;Peyron et al, 2006;Morisset et al, 2008;Sousa et al, 2008;Sousa et al, 2009). However, due to the limitation of serotyping it is not possible to differentiate type II from non-type II strains particularly in South America where there is a high diversity of T. gondii strain types.…”
Section: Other Diagnostic Methodsmentioning
confidence: 99%
“…Genetic analyses have shown that the vast majority of all T. gondii-strains typed to date fall into one of three clonal lineages, type I, II, and III (Howe & Sibley, 1995), which differ in virulence but do not show clear host or geographic boundaries (Lindström et al, 2006). Studies from different parts of the world have produced similar findings in which the genotyping of the SAG2-locus revealed that the type II allele was the most disease-causing strain (reactivation of chronic infections) found in immunocompromised individuals (Dardé et al, 1992;Howe and Sibley, 1995;Howe et al, 1997;Fuentes et al, 2001;Lindström et al, 2006;Ajzenberg et al, 2009). This high prevalence of type II strains in human toxoplasmosis may simply reflect the source of the strains that led to human infections (Howe et al, 1997).…”
Section: Epidemiology -From Source To Genementioning
confidence: 97%
See 1 more Smart Citation
“…The Fmoc protecting group was removed by using a mild base treatment with 2% piperidine 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) in dimethyl sulfoxide-70% domethylformamide with in situ activation. The peptide sequence chosen for SAG-1 is based in KATO et al 19 ; for GRA-1 in BEGHETTO et al 3 ; and for GRA-7 in SOUSA et al 31 .…”
Section: Pagementioning
confidence: 99%
“…Several studies have shown that synthetic peptides can be used for the serological diagnosis of viral and bacterial as well as parasitic diseases (1,31,36,44,46,54). Large amounts of synthetic peptides can be produced with a high level of purity within a relative short period of time.…”
mentioning
confidence: 99%